PENGKLARIFIKASIAN DAMPAK FUNGSI SDM PADA KINERJA ORGANISASI-HR SCORECARD - Vip Paramarta; Hadiansyah; Moh Arif Kusnadi; Andika Fajar Nugroho; Olivia Melissa Poluan (JURNAL RISET MANAJEMEN (JURMA), 2023)
Previous research or what is commonly referred to as relevant research is very important in a study or what is commonly referred to as a scientific article, to further strengthen theories and phenomena regarding the relationship or influence between variables. This article reviews the facts that affect organizational performance-HR Scorecard. HR is an individual who works as a driving force for an organization, both an institution and a company and functions as a capability asset whose capabilities must be trained and developed. Organizational performance is the effectiveness of the organization as a whole to meet the predetermined needs of each relevant group through systematic efforts and continuous improvement of organizational capabilities. So that quality human resources can produce better performance from an organization and in accordance with the goals and functions of a company. Moreover, in line with the existence of an HR Scorecard that can control and supervise HR to always implement the vision, mission and goals of the organization in achieving organizational goals.